Mekanisme Proses Pembuatan “Tahu Sari” Gundik Dengan Mesin Uap (Boiler) - Sulung Cahyaning T; Ahmad Kirom (Social Science Academic, 2025)
This study aims to describe the business management of the "tofu sari" factory in Gundik, Slahung, Ponorogo. This research uses the ABCD (Asset Based Community Development) method, which prioritizes the benefits of assets and the potential that exists in the village and is owned by the community. The research informants are administrators, as well as tofu sari factory workers. The results of this study are the mechanism of the process of making tofu with a steam engine (boiler), human resource management that has been through trials (training) of workers and machine technicians who were brought in from Klaten, Central Java, and excellence taboo factory uses modern machines that will maintain the taste of tofu, and the weakness is that there are tofu products that fail when there is damage to the machine during the cooking process.